2006
DOI: 10.1152/ajprenal.00366.2004
|View full text |Cite
|
Sign up to set email alerts
|

Zinc protects renal function during cadmium intoxication in the rat

Abstract: This study investigates the effect in the rat of chronic CdCl2 intoxication (500 μg Cd2+/kg, daily ip injection for 5 days) on renal function and the changes in tight junction proteins claudin-2, claudin-3, and claudin-5 present in rat kidney. We also studied the effect of coadministration of ZnCl2 (500 μg Zn2+/kg) during chronic CdCl2 intoxication. Our results indicate that 1) most of the filtered Cd2+ is reabsorbed within the kidney; 2) chronic Cd2+ intoxication can induce a change in renal handling of ions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
73
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 47 publications
8
73
0
2
Order By: Relevance
“…Our results were in agreement with those previously reported [9,24,46,51,53] which postulated that, Zn play an important rule in preventing the oxidative stress, apoptosis and the necrosis induced by Cd. Moreover, in a plant study.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results were in agreement with those previously reported [9,24,46,51,53] which postulated that, Zn play an important rule in preventing the oxidative stress, apoptosis and the necrosis induced by Cd. Moreover, in a plant study.…”
Section: Discussionsupporting
confidence: 94%
“…Our results were in agreement with published data [46] which reported that the effect of co-treatment with Zn during Cd administration completely prevented the changes in renal function produced by the toxic metal in the rat, even though they did not find any significant difference in the renal Cd content. There is considerable information in the literature regarding the protective eff ect of Zn against the cellular toxicity caused by Cd.…”
Section: Discussionsupporting
confidence: 93%
“…Renal conversion of 25-hydroxycholealceferol to 1, 25-dihydroxycholecalceferol in rats is inhibited by low and a high dietary concentration of cadmium [57] . The present results agree with a series of studies in Japan, described in detail in WHO [58] , on the effect of dietary cadmium in monkeys, a dose of (30 mg kg −1 bwt) was found to worsen osteomalacic changes in the bones of animals fed diets with low concentration protein, calcium and vitamin D. Several studies on the effects of oral administration of cadmium on bone and calcium metabolism showed decreased calcium content in bone and increased urinary excretion of cadmium that resulted in decalcification and cortical atrophy in the skeleton, associated with renal cortical concentrations [59][60][61] . In the present study, Camel's milk improved the negative effect of cadmium on calcium metabolism and demonstrate protective action against the changes of calcium metabolism by cadmium, Calcium levels significantly increased in the rats orally administered Camel's milk with cadmium compared to rats received cadmium alone orally.…”
Section: Discussionmentioning
confidence: 99%
“…Later research of acute Cd exposure showed that Zn inhibited Cd transport along the terminal nephron segments in rats and vice versa (65). Jacquillet et al (66) confirmed that Zn addition during Cd exposure prevented metal-induced changes in rat renal functions. Dietary Zn supplementation may also prevent Cd-induced disorders in bone turnover.…”
Section: Zinc and Cadmium Interactionmentioning
confidence: 97%